Piezoelectricity enhancement of P(VDF/TrFE) by X-ray irradiation - Pilet, Nicolas; Khikhlovskyi, Vsevolod; Breemen, Albert J. J. M. van; Michels, Jasper J.; Kemerink, Martijn; Gelinck, Gerwin; Warnicke, P.; Bernard, Laetitia (Organic electronics, 2016)
Organic electronics is becoming more and more important because the low level of fabrication and deposition complexity even at large scale makes it a good candidate for future low cost technological product development. P(VDF-TrFE) is a co-polymer of special interest due its ferroelectric property enabling usage in re-programmable non-volatile organic memory and magnetoelectric sensors. Piezo force microscopy (PFM) provides access to the technologically relevant ferroelectric polarisability and its remanent polarization via imaging of the piezoelectric property. Here we use PFM to show that piezoelectric response of a P(VDF-TrFE) film can be enhanced by up to 260 % after soft X-ray irradiation. This enhancement correlates with morphological change of part of the film, from amorphous to crystalline. An optimal irradiation dose is found above which the film gets eroded and the piezoelectric response gets lowered.